Water leakage detection monitoring and controlling system using IOT - Swetha Reddy, P; V.Chanakya, K; Eswari, B; Bhupati, Ch (International Journal of Engineering and Technology, 2018)
The Water is the most valuable because it is a basic need of all humans, in these days water supply department are facing problem because of less amount of water due to less rainfall, lowering of ground water in spite of all these problems water leakage from pipelines while supplying and also no monitoring of water distribution and controlling. With increment in population, neighborhoods have expanded as a result of this reason water has turned into a major issue which influences in distribution, conservation, consumption and also the quality so, to overcome all these problems and create system economical thereâ€™s want ofÂ  correct observance and dominant system. In this paper, we are proposing a system which can detect the leakages, monitoring and controlling if water supply in pipelines. Sensors places in the tank which continuously informs the water level of water in the tank. The motor functioning will be automatically turn on and when tank is about to fill up it will cut off.